KEPATUHAN DIET DENGAN KADAR GLUKOSA DARAH PADA LANSIA DIABETES MELLITUS DI PUSKESMAS SANGKRAH KOTA SURAKARTA - Sari, Nuraini Atika; Soviana, Elida (Indonesian Journal of Nutrition Science and Food; Vol 1 No 2 (2022): Januari 2022, 2022)
Diabetes mellitus is a metabolic disease characterized by hyperglycemia resulting from impaired insulin secretion, insulin action or both. One of the factors that can affect blood glucose levels is dietary compliance. The term that is often used in DM diet compliance is "the right 3J principle" which is the right number of calories, the right type of food and/or food, and the right meal schedule. The purpose of this study was to determine the relationship between dietary compliance with blood glucose levels in DM elderly at Sangkrah Health Center Surakarta City. This type of research uses an observational design with a cross-sectional approach. The research site was at the Sangkrah Public Health Center, Surakarta with a total sample of 49. Data on dietary compliance were obtained using a 24-hour food intake recall form and data on blood glucose levels using an accu-check glucometer. Data analysis used the Pearson Product Moment correlation test. The results showed that the level of diabetes mellitus diet adherence in the elderly at Sangkrah Health Center, there were 27 research subjects (55.1%) who adhered to the DM diet. Blood glucose levels in the elderly at the Sangkrah Health Center were obtained, there were 36 research subjects (73.5%) elderly in the normal category. The conclusion of this study was that there was no significant relationship between dietary compliance with blood glucose levels in the elderly with diabetes at Sangkrah Public Health Center Surakarta with a p-value of 0.617.